A VANTAGEM PECUNIÁRIA NOS DANOS AMBIENTAIS: ADICIONALIDADE ÀS ANÁLISES PELO MINISTÉRIO PÚBLICO DO ESTADO DO RIO DE JANEIRO - Maneschy, Luís Otávio Guimarães (2012)
The Constitution proclaims that the pursuit of environmental protection lies with the Public Ministry, under the Union and States. The proposed work aims to contribute in improving the performance of the Public Ministry of the State of Rio de Janeiro in this mission. Through the verification of pecuniary advantage received by agents that cause environmental damage, considered an aggravating factor in the application of the penalty Environmental Crimes Act, intended to examine the possibility of adding new procedures to the Prosecutor of Justice Trusteeship Collective Environment, increasing the management of their proof technique and contributing to an enrichment analysis in civil context, in civil investigations and civil suits. The research is exploratory characteristics, including literature review, interviews with Prosecutors, critical assessment of pecuniary advantage in the case study and its applicability and relevance in different types of events that cause environmental damage. Given the originality of the research and its correlation with the theme environmental valuation, observed by the author in his role as technical expert of the Public Ministry of the State of Rio de Janeiro, it is hoped that the results will also help in analysis methodologies developed in Public Ministry from other states.